COMPARATIVE ADVANTAGE OF SIAMESE ORANGE (Citrus Nobilis) FARMING IN DISTRICT OF 50 KOTA, WEST SUMATERA - M. Mustopa Romdhon; Apri Andani; Wahyu Fitri Nasari (AGRITROPICA : Journal of Agricultural Sciences, 2018)
Citrus Nobilis, known as Siamese orange, is one of the strategic fruits commodities for West Sumatera because of its higher productivity, approximately 6 - 9 tons per hectare. However, this commodity faces a fluctuated demand both in domestic and international markets. This is a serious problem due to its impact on farm income as well as in its competitive advantage. The aim of this study was to analyze the comparative advantage level of siamese orange farming.  Survey of 84 siamese orange farmers selected using simple random sampling is conducted to get orange farming data. The comparative advantage level is measured using Policy Analysis Matrix (PAM) approach. The results show that siamaese orange farming has a high comparative advantage. This showed by a value of social profitability was more than zero and domestic resource cost ratio was less than one. This comparative advantage could be sustainable by domestic resources utilization efficiently. The improvement of skills and the use of modern siamaese orange farming technology are recommended.Keywords: Comparative advantage, siamese orange farming, PAM